Determination of Uranium Concentration in Soil of Baghdad Governorate and its Effect on Mitotic Index Assay - Q. Mryoush, Atheer .; M. Salim, Hiba. (Iraqi Journal of Science, 2023)
The aim of this work is to determine the uranium concentration in soil samplestaken from the north, south, east, west and center of the city of Baghdad andmeasure its impact on the rate of cell division for non-smokers peoples and living inthose areas and that between the ages 25-30 year.The uranium concentration in the samples determined by using CR-39 trackdetector . As calculated for the ten samples of each site when irradiated by thermalneutrons from the (Am - Be) source with flux (5x 103 n S-1cm-2), the concentrationvalues were calculated by a comparison with standard geological samples. Theresults indicate that the extent of the concentration of uranium in the soil north andeast of Baghdad was 12.9 ± 0.7 in Al- Taji north of Baghdad and 12.4 ± 0.23ppmin the Diyala- Bridge area east of Baghdad and the results were recorded lowerconcentration of uranium in the western, central and southern Baghdad, which stoodat 0.60 ± 0.21 in the Abu Ghraib area west of Baghdad, and 4.6 ± 0.7ppm in theBab-Al-Sharqee of central Baghdad and 0.87 ± 0.7ppm in Al-Mhmodya area southof Baghdad . The mitotic index assay MI in the north and east of Baghdad was 2.3 ±0.059 in the north and 2.43 ± 0.059 in eastern Baghdad, while the lowest rate inWest and Central and South compared with the threshold level of 0.6 . Whichindicates contamination north and east of Baghdad as a result of uranium wars onIraq passed in 2003 which negatively affects the behavior of lymphocytes and onthe rate of division.